HUBUNGAN ANTARA SELF-CONCEPT DENGAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Riki Musriandi (Jurnal Dedikasi Pendidikan, 2017)
This study examined the relationship between self-concept and students' mathematical problem solving abilities. This was conducted in Madrasah Tsanawiyah Negeri (MTsN) Kota Banda Aceh. The method in this research was survey method with correlation technique that is looking for the relationship between self-concept with students’ mathematical mass solving ability. The population of the study was all the students class VIII. The sample in this research was the students of class VIII-10 and VIII-11 which consisted to 54 students based on the results of considerations submitted principals and teachers of mathematics study at the school. The hypothesis in this research is “There is a relationship between self-concept and mathematical problem-solving abilities”. The instruments used are self-concept scales and students' mathematical problem-solving tests. The results showed that there is a positive and significant relationship between self-concept with students' mathematical problem solving abilities. The contribution given by the self-concep variable to the mathematical problem solving ability is 24.6% and the rest is influenced by other factors or variables.